2021
DOI: 10.3389/fmicb.2021.709855
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Genomic Analysis of Rouxiella badensis SER3 as a Novel Biocontrol Agent of Fungal Pathogens

Abstract: In recent decades, various bacterial species have been characterized as biocontrol agents for plant crop diseases; however, only a few genera have been predominantly reported in the literature. Therefore, the identification of new antagonists against phytopathogens is essential for boosting sustainable food production systems. In this study, we evaluated the role of strain SER3 from the recently discovered Rouxiella badensis as a biocontrol agent. SER3 was isolated from the phyllosphere of decaying strawberry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…Strains in the Bacillus genus have been frequently used in commercial biopesticide development on soft fruits. Of particular interest is the genus Rouxiella ; an in vitro study showed that specific Rouxiella strains successfully controlled common pathogens of strawberries (Morales‐Cedeño et al, 2021). This genus was more prevalent on the later fruit development stages (when Cladosporium was noted to decrease); hence, further investigations into the antagonism of this genus against Cladosporium may be warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Strains in the Bacillus genus have been frequently used in commercial biopesticide development on soft fruits. Of particular interest is the genus Rouxiella ; an in vitro study showed that specific Rouxiella strains successfully controlled common pathogens of strawberries (Morales‐Cedeño et al, 2021). This genus was more prevalent on the later fruit development stages (when Cladosporium was noted to decrease); hence, further investigations into the antagonism of this genus against Cladosporium may be warranted.…”
Section: Discussionmentioning
confidence: 99%
“…R. badensis has not been previously reported to suppress GER disease in maize to the best of our knowledge. It has been reported as a novel biocontrol agent against the postharvest fungal pathogens Botrytis cinerea and Fusarium brachygibbosum in strawberry fruit, affecting mycelial development ( Morales-Cedeño et al., 2021 ). It also showed different levels of in vitro antagonism against 20 fungal pathogens in berries ( Morales-Cedeño et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported as a novel biocontrol agent against the postharvest fungal pathogens Botrytis cinerea and Fusarium brachygibbosum in strawberry fruit, affecting mycelial development ( Morales-Cedeño et al., 2021 ). It also showed different levels of in vitro antagonism against 20 fungal pathogens in berries ( Morales-Cedeño et al., 2021 ). Here, we showed that R. badensis (AS112) seemed to colonize wound sites on silks more than Fg hyphae.…”
Section: Discussionmentioning
confidence: 99%
“…Rouxiella badensis is a Gram-negative bacterium in the family Yersiniaceae ( 1 ) found associated with soil and plant ecosystems ( 2 ), with emerging applications including post-harvest preservation of berries ( 3 ), a human antidepressant probiotic ( 4 6 ), biosynthesis of L-asparaginase ( 7 ), and uncharacterized antibiotics ( 8 ). High-quality genome sequences, such as described here, allow improved identification of metabolic pathways and secondary metabolite prediction ( 9 , 10 ).…”
Section: Announcementmentioning
confidence: 99%